Ethylene-Induced Hydrogen Sulfide Negatively Regulates Ethylene Biosynthesis by Persulfidation of ACO in Tomato Under Osmotic Stress - Jia, Honglei; Chen, Sisi; Liu, Dan; Liesche, Johannes; Shi, Cong; Wang, Juan; Ren, Meijuan; Wang, Xiaofeng; Yang, Jun; Shi, Wei; Li, Jisheng (Frontiers in Plant Science, 2018)
A number of recent studies identified hydrogen sulfide (H2S) as an important signal in plant development and adaptation to environmental stress. H2S has been proven to participate in ethylene-induced stomatal closure, but how the signaling pathways of H2S and ethylene interact is still unclear. Here, we reveal how H2S controls the feedback-regulation of ethylene biosynthesis in tomato (Solanum lycopersicum) under osmotic stress. We found that ethylene induced the production of H2S in guard cells. The supply of hypotaurine (HT; a H2S scavenger) or DL-pro-pargylglycine (PAG; a synthetic inhibitor of H2S) removed the effect of ethylene or osmotic stress on stomatal closure. This suggests that ethylene-induced H2S is a downstream component of osmotic stress signaling, which is required for ethylene-induced stomatal closure under osmotic stress. We further found that H2S inhibited ethylene synthesis through inhibiting the activity of 1-aminocyclopropane-1-carboxylic acid (ACC) oxidases (ACOs) by persulfidation. A modified biotin-switch method (MBST) showed that H2S can induce persulfidation of LeACO1 and LeACO2 in a dose-dependent manner, and that persulfidation inhibits the activity of LeACO1 and LeACO2. We also found that LeACO1 is persulfidated at cysteine 60. These data suggested that ethylene-induced H2S negatively regulates ethylene biosynthesis by persulfidation of LeACOs. In addition, H2S was also found to inhibit the expression of LeACO genes. The results provide insight on the general mode of action of H2S and contribute to a better understanding of a plant’s response to osmotic stress.